SYNTHESIS, CHARACTERIZATION AND STUDY OF SURFACTANTS EFFICIENCY IN THE DISPERSION (O/W) EMULSIONS - Al-Assadi, Muhanned; Al-Ali, Kaukab (Iraqi Journal of Science, 2024)
In the present study three classes of surfactants derivatives from benzillic acid were prepared. The prepared surfactants were characterized by FTIR-Infrared spectrophotometer and CHN analysis. The physical properties of the prepared surfactants were measured i.e. (pH, density, viscosity, color, freezing point and stability to hydrolysis). The efficiency of the prepared surfactants was studied with time and long side chain substituted. The hydrophilic-lipophilic balance (HLB) was calculated.